Valoración De La Composición Química De Fermentación Y Degradabilidad Ruminal In Vitro De Dietas Con Diferentes Inclusiones De Harina De Banano Y Urea - Espinoza, Víctor Godoy; Cevallos, Juan Avellaneda (European Scientific Journal, ESJ, 2016)
The purpose of this study was to evaluate the chemical of in vitro ruminal fermentation of diets with different inclusions of banana flour and urea. The assessment and in vitro fermentation were performed in the laboratory of nutrition and metabolism Rumiologia Faculty of Animal Science. In the first phase the chemical composition is performed in the second stage fermentation in vitro degradability It was a desing completely random was applied, with four diets and four replications; repetition consisted of a bottle or container or in vitro digestibility. Each bottle will be an experimental unit represent a repetition. Data were analyzed using the statistical package procedure Eva DE-A-Dva and mean differences were compared using the Tukey test (p <0.05). The degradability of dry matter (DM) of the diet obtained in this study confirm the disappearance of nutrients as time passes (2, 6, 14, 24, 36, 48, 72 hours) reaching values above 70% digestibility which guarantees the quality of the diet. The pH in the rumen fermentation in vitro obtained in this research on diet with inclusions of banana flour and urea from 0 to 6 and 6 to 72 hours is not dropped to dangerous levels of critical thresholds for celulolisis.